Missing Bullets: Bullet Embolization Case Series and Review of the Literature. (April 2023) - Castater, Christine; Noorbakhsh, Soroosh; Harousseau, William; Klingensmith, Nathan; Koganti, Deepika; Nguyen, Jonathan; Smith, Randi N.; Benarroch-Gampel, Jaime; Ramos, Christopher R.; Rajani, Ravi; Sciarretta, Jason D.
Purpose: Bullet embolization is a rare but dangerous phenomenon. Based on the location of embolization, migration of bullets can cause limb or intra-abdominal ischemia, pulmonary infarction, cardiac valve injury, or cerebrovascular accident. Bullet emboli can present a diagnostic challenge given the varied nature of complications based on location of embolization, which may not coincide with the site of initial injury. The purpose of this study is to present several cases of bullet embolization from our busy urban trauma center and make recommendations for management. Methods: We present 3 cases of bullet embolization seen in injured patients at our Level 1 trauma center. We describe our management of these injuries and make recommendations for management in the context of our institutional experience and comment on the available literature regarding bullet embolization. Results: Two of our patients presented in extremis and required operative intervention to achieve stability. The intravascular missile was discovered intraoperatively in one patient and removed in the operating room, while the missile was discovered on postoperative imaging in another patient and again removed operatively after an unsuccessful attempt at minimally invasive retrieval. Our third patient remained hemodynamically stable throughout his hospitalization and had endovascular management of his bullet embolus. Conclusion: Bullet emboli present a challenging complication of penetrating trauma. We recommend removal of all arterial bullet emboli and those within the pulmonary venous system. In hemodynamically stable patients, we recommend initial attempts of endovascular retrieval followed by open surgical removal. We recommend open removal in cases of hemodynamic instability.